(3GdJCejfGJ Ydi GdCTNGU hOhQgG aj GdGONGQ GdhWfj (B/s - (3eMOjO, edjcIs ((3JdeSGf(B: s (3GdecJH GdLGeYj GdMOjK(B, s, 2017)
(3jVe JWHjbGJ JCejfGJ Ydi GdCTNGU Ydi GdeSJhi GdYGdej, GdGQJHGW GdhKjb dCShGb GdJCejfGJ GdOhd GdZQHjI, CShGb JCejfGJ GdCTNGU YfO GdHdOGf GdSGFQI aj WQjb Gdfeh, JRGhL hJbGQH GdLgGR GdeUQaj HGdJCejf hJLQHI Hfhc GdJCejf aj GdYGde, JLQHI GdLRGFQ aj GdJCejfGJ Ydi GdCTNGU hebGQfJgG eY GdOhd GdeZGQHjI, GdecGfI GdGbJUGOjI hGdGLJeGYjI dJCejfGJ GdCTNGU aj GdLRGFQ, JWHjbGJ JCejfGJ GdCTNGU aj GdLRGFQ hebGQfJgG HGdOhd GdeZGQHjI, BaGb JWhjQ Hfc GdJCejf YfO GdOhd GdeZGQHjI YeheG hGdLRGFQ NUhUGs
(3HHdjhZQGajG(B: (3U(B.325-327s
Keywords: (3GdEONGQs; (3GdJCejf (B- (3GdHfhcs; (3GdJCejf Ydi GdCTNGUs